Making a Place for Pragmatics in Art and Aesthetics in Architecture - Thakur, Anubhuti (Nurture, 2007)
Long standing views about art and architecture have differentiated the basic premise for their existence as aesthetics and pragmatics respectively. This paper is based on the premise that architecture must learn its aesthetic aspects from pragmatism in art to fulfill its pragmatic purposes and art must adopt the purposefulness inherent in architecture to assign meaning to aesthetic experience. Questions are raised and an attempt is made to answer the same through identification, and redefinition of certain theories to apply them to architecture and to today’s social, cultural, and political scenario. Suggestions are made for architecture classrooms to exploit the wealth of scholastic insight available on pragmatism and neo-pragmatism in art education.